Czynniki stresogenne wśród studentów filologii rosyjskiej w kontekście aktualnej sytuacji geopolitycznej - Dziedzic, Małgorzata (Studia Rossica Posnaniensia, 2025)
The aim of this article is to identify the background as well as types of stressors and their impact on the acquisition of Russian as a foreign language by students of Russian Philology in the current geopolitical situation. Determining the causes of stress and the correlation between perceived stress level and academic achievement of students can help to identify areas that require support and indicate possible ways to improve the situation. Based on the conducted questionnaire survey, observation during classes and the literature on stress and its impact on the learning process, the author attempted to identify the most important internal and external factors causing academic stress and examined the influence of the current geopolitical situation and social determinants on the stress level experienced by Russian philology students. In addition, the degree of learners’ awareness of opportunities to reduce their stress levels was investigated. The results of the research made it possible to identify particularly common sources of stress and contributed to the identification of possible ways to reduce its level. Examples of stress reduction methods that are beneficial in language acquisition, good practices of institutional activities as well as interpersonal skills of the lecturers that can contribute to the improvement of the current situation are recommended.